Cuidado paliativo e educação: percepções da equipe multiprofissional de um hospital de alta complexidade da grande São Paulo - Reis, Ana Cláudia Arguelles dos [UNIFESP] (2018)
The aim of this research was to analyse the insights of the multi-professional team regarding the practices of the palliative care ward of the Santa Marcelina Hospital in Itaquera, which is categorized as a high complexity hospital in Greater São Paulo, Brazil. Other objectives included: to report the views of the professionals of the multi-professional team in relation to the process of work performed in a Palliative Care ward, identifying the observations of this team when facing the death of the hospitalized patient, in addition analyzing how to disseminate the concepts of Palliative Care for the professionals who carry out internship in this ward, by means of educational initiatives.For this purpose, a descriptive exploratory study with a qualitative approach was performed, having as data collection tools and as a suggestion from the Examining Body, the implementation of two focus groups carried out on 20/06/2017, for the supplementation of data and the possibility of bringing other experiences to the data collected, allowing for a more comprehensive look at the multi-professional team. On 08/02/2018 the second focus group meeting was held with the professionals who work in the palliative care team. These included: 02 Preceptors, 01 Nurse, 01 Physiotherapist, 01 Audiologist, 01 Dietitian, 03 Medical Residents and 03 Residents of the Multi-Professional Hematologic Oncology team, by way of approval from the Research Ethics Committee at UNIFESP and the Santa Marcelina Hospital in Itaquera. The content analysis and themed modality was developed in focus groups from 03 themed cores: the Palliative Care Ward, End of Life and Education in Palliative Care, with 153 (one hundred and fifty three) content units and 209 (two hundred and nine) registry units, from which there emerged 07 (seven) categories and 08 (eight) sub-categories. The data analysis showed that the multi-professional team, despite consisting of professionals who work in the Palliative Care Ward throughout periods which vary from 03 months to 04 years, maintain a good relationship and professional respect. It was possible to conclude that there is good interaction between the members of the multi-professional team, with the exchanging of experiences, active listening, respect for other’s opinions, search for knowledge and willingness to disseminate Palliative Care knowledge to other wards and the Emergency Department of the Hospital. However, this is an initial project, that is to say, the beginning of a discussion to provide educational initiatives to the Palliative Care professionals, in order to improve the working process, provide comfort to the patients, in addition to the extended care of their families and also to the multi-professional team. This included caring for the physical and mental health of the team, to avoid illnesses such as Burnout Syndrome.